Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

A memory-constrained multiscale pore network modeling framework for gas permeability prediction in compacted bentonite - Yongxiao Qu; Huaxiang Yan; Bo Li; LiGe Wang; Andrey P Jivkov; Weiguang Wang; Lin Ma; Mohsen Masihi; Qingrong Xiong (Computers and Geotechnics, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Medicinal seahorses (Hippocampus spp.) for Alzheimer’s disease within species conservation framework: an integrated review of ethnopharmacology, bioactivity, bibliometrics, and network pharmacology - Peng Song; Mengyu Wang; Tao Liu; Zhuoqing Zhang; Xia Ren; Yao Liu; Jerome P. L. Ng; Vincent Kam Wai Wong; Betty Yuen Kwan Law; Xianjun Fu; Liqun Qu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metabolomic signatures of extreme old age: findings from the New England Centenarian Study - Stefano Monti; Michael S. Lustgarten; Ziwei Huang; Zeyuan Song; Mengze Li; Dylan Ellis; Qu Tian; Luigi Ferrucci; Noa Rappaport; Stacy L. Andersen; Thomas P. Perls; Paola Sebastiani (GeroScience, 2026)

The relative importance of multiple environmental factors on river macroinvertebrate abundance across different groups based on a nationwide dataset from England - Dinara Sadykova; Andrew C. Johnson; Yueming Qu; Peter A. Henrys; Monika D. Jürgens; Virginie D.J. Keller; Nuria Bachiller-Jareno; Peter M. Scarlett; Michael G. Hutchins; Lisa Gecchele; Alexander Sadykov; John P. Sumpter; et al. (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of roads on animals and mitigation measures in Asia - Haotong Su; Yun Wang; Qilin Li; Yangang Yang; Abudusaimaiti Maierdiyali; Shuangcheng Tao; Yaping Kong; Jiding Chen; Jiapeng Qu; Yongshun Han; Aili Kang; Shu Chen; et al. (Biological Conservation, 2026)

Genomic Evidence for Elevational Segregation and Adaptive Introgression in Prunellidae Radiation - Xinlai Wu; Wenqing Zang; Per G. P. Ericson; Yanhua Qu (Molecular Ecology, 2026)
Heterogeneous mountainous environments and climate fluctuations during glacial periods can accelerate speciation and adaptive evolution in mountainous species. However, the interplay between these processes and their collective impact on mountainous diversity remains poorly understood, particularly across broad geographic scales. We conducted a comparative genomic study of Prunellidae (accentors), an avian family distributed across Eurasian mountain chains. Our analyses revealed low genetic divergence among species ( D XY ranging from 0.631 × 10 −2 to 2.665 × 10 −2 ). When separated by elevation, high‐elevation species (> 2500 m) exhibited greater genetic diversity than mid‐ (1000–2500 m) and low‐elevation species ( 1000 m). Demographic reconstructions showed distinct response to Last Glacial Maximum: high‐elevation species experienced population declines, mid‐elevation species maintained stable population sizes, while low‐elevation species underwent expansions. High‐elevation species also showed signatures of divergent selection in genes involved in blood vessel development and DNA break repair, suggesting adaptation to extreme environments. Despite these differences, we detected widespread interspecific introgression, with the most pronounced event occurring between low‐elevation P. montanella and the ancestor of high/mid‐elevation species. The introgressed regions showed evidence of positive selection and reduced genetic load, potentially facilitating P. montanella 's recent expansion into higher elevations. Our findings demonstrate how elevational segregation drives montane diversity and underscore the importance of adaptive introgression in the evolution of the montane species.

Performance comparison of capped pile and piled beam support systems for embankments on soft soils - Tengfei Wang; Shujun Qu; Keqin Huang; Kaiwen Liu; David P. Connolly; Qiang Luo (Transportation Geotechnics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Temporal species stability underpins the link between biodiversity and human health - Qiaochu Xu; Bingjie Qu; Peng Zhao; Sarah Clement; Yuan Shi; Kelvin P. Jordan; Li Li; Ying Chen (Environmental Research, 2025)

PP2A attenuates α-amanitin-induced liver injury by promoting autophagy and inhibiting apoptosis in mouse models - Hui Xu; Jian Sun; Yu Zhao; Yaxiong Zhou; Kuan Wang; Xiang Liu; Jieyan Yang; Peng Wu; Shengkui Wang; John P. Kastelic; Weijie Qu; Limei Zhang; et al. (Chemico-Biological Interactions, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Increasing humification and reducing CH4 emission during rice straw fermentation: the role of Streptomyces rochei ZY-2 - B. Fu; B. Gao; J. Zhang; H. Huang; Z. Wei; Q. Wang; P. Qu (International Journal of Environmental Science and Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Iron-loaded activated carbon cloth as CDI electrode material for selective recovery of phosphate - Tanzila Sharker; Jayaruwan G. Gamaethiralalage; Qiyang Qu; Xinxin Xiao; Jouke E. Dykstra; Louis C. P. M. de Smet; Jens Muff (Environmental Science and Pollution Research, 2024)
This study investigated the efficacy of oxidised iron-loaded activated carbon cloth (Fe-ACC) for selective recovery of phosphorous. The capacitive deionisation (CDI) technology was employed, for rapid removal of phosphate, with the aim of reducing the reliance on high alkalinity environment for the regeneration of Fe-ACC electrode. Multiple experimental parameters, including applied potential, pH, and co-existing ions, were studied. Additionally, the CDI system was tested on a real water matrix (Lake Ormstrup, Denmark) to elucidate the electrodes’ performance on selective recovery of phosphate. About 69 ± 10% of the adsorbed phosphate were released at pH 12 via pure chemical desorption, which was ~ 50% higher than that at pH 9. The CDI system successfully demonstrated the selective removal of phosphate from the lake water. It reduced the concentration of phosphate from 1.69 to 0.49 mg/L with a 71% removal efficiency, while the removal percentages of other anions, namely chloride, sulphate, bromide, nitrite, nitrate, and fluoride, were 10%, 7%, 1%, 1.5%, 4%, and 7%, respectively.

The effect of cross-regional transport on ozone and particulate matter pollution in China: A review of methodology and current knowledge - Kun Qu; Yu Yan; Xuesong Wang; Xipeng Jin; Mihalis Vrekoussis; Maria Kanakidou; Guy P. Brasseur; Tingkun Lin; Teng Xiao; Xuhui Cai; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2024)

The Diversity of Artificial Intelligence Applications in Marine Pollution: A Systematic Literature Review - Jia Ning; Shufen Pang; Zainal Arifin; Yining Zhang; U. P. K. Epa; Miaomiao Qu; Jufen Zhao; Feiyang Zhen; Abhiroop Chowdhury; Ran Guo; Yuncheng Deng; Haiwen Zhang (Journal of Marine Science and Engineering, 2024)
Marine pollution, a major disturbance to the sustainable use of oceans, is becoming more prevalent around the world. Multidimensional and sustainable ocean governance have become increasingly focused on managing, reducing, and eliminating marine pollution. Artificial intelligence has been used more and more in recent years to monitor and control marine pollution. This systematic literature review, encompassing studies from the Web of Science and Scopus databases, delineates the extensive role of artificial intelligence in marine pollution management, revealing a significant surge in research and application. This review aims to provide information and a better understanding of the application of artificial intelligence in marine pollution. In marine pollution, 57% of AI applications are used for monitoring, 24% for management, and 19% for prediction. Three areas are emphasized: (1) detecting and responding to oil pollution, (2) monitoring water quality and its practical application, and (3) monitoring and identifying plastic pollution. Each area benefits from the unique capabilities of artificial intelligence. If the scientific community continues to explore and refine these technologies, the convergence of artificial intelligence and marine pollution may yield more sophisticated solutions for environmental conservation. Although artificial intelligence offers powerful tools for the treatment of marine pollution, it does have some limitations. Future research recommendations include (1) transferring experimental outcomes to industrial applications in a broader sense; (2) highlighting the cost-effective advantages of AI in marine pollution control; and (3) promoting the use of AI in the legislation and policy-making about controlling marine pollution.

Determining the response of ecological drought to meteorological and groundwater droughts in Northwest China using a spatio-temporal matching method - Tianliang Jiang; Xiaoling Su; Yanping Qu; Vijay P. Singh; Te Zhang; Jiangdong Chu; Xuexue Hu (Journal of Hydrology, 2024)

Variations in isoprenoid tetraether lipids through the water column of the Western Pacific Ocean: Implications for sedimentary TEX86 records - Jinqiang Guo; Zongyue Wang; Eric P. Achterberg; Huamao Yuan; Jinming Song; Yuning Wang; Xuegang Li; Liqin Duan; Baoxiao Qu (Geochimica et Cosmochimica Acta, 2024)

Miscarriage risk assessment: a bioinformatic approach to identifying candidate lethal genes and variants - Mona Aminbeidokhti; Jia-Hua Qu; Shweta Belur; Hakan Cakmak; Eleni Jaswa; Ruth B. Lathi; Marina Sirota; Michael P. Snyder; Svetlana A. Yatsenko; Aleksandar Rajkovic (Human Genetics, 2024)
Purpose Miscarriage, often resulting from a variety of genetic factors, is a common pregnancy outcome. Preconception genetic carrier screening (PGCS) identifies at-risk partners for newborn genetic disorders; however, PGCS panels currently lack miscarriage-related genes. In this study, we evaluated the potential impact of both known and candidate genes on prenatal lethality and the effectiveness of PGCS in diverse populations. Methods We analyzed 125,748 human exome sequences and mouse and human gene function databases. Our goals were to identify genes crucial for human fetal survival (lethal genes), to find variants not present in a homozygous state in healthy humans, and to estimate carrier rates of known and candidate lethal genes in various populations and ethnic groups. Results This study identified 138 genes in which heterozygous lethal variants are present in the general population with a frequency of 0.5% or greater. Screening for these 138 genes could identify 4.6% (in the Finnish population) to 39.8% (in the East Asian population) of couples at risk of miscarriage. This explains the cause of pregnancy loss in approximately 1.1–10% of cases affected by biallelic lethal variants. Conclusion This study has identified a set of genes and variants potentially associated with lethality across different ethnic backgrounds. The variation of these genes across ethnic groups underscores the need for a comprehensive, pan-ethnic PGCS panel that includes genes related to miscarriage.

Significant improvement in freshwater invertebrate biodiversity in all types of English rivers over the past 30 years - Yueming Qu; Virginie Keller; Nuria Bachiller-Jareno; Michael Eastman; Francois Edwards; Monika D. Jürgens; John P. Sumpter; Andrew C. Johnson (Science of The Total Environment, 2023)

Mutant p53R211* ameliorates inflammatory arthritis in AIA rats via inhibition of TBK1-IRF3 innate immune response - Yaling Zeng; Jerome P. L. Ng; Linna Wang; Xiongfei Xu; Betty Yuen Kwan Law; Guobing Chen; Hang Hong Lo; Lijun Yang; Jiujie Yang; Lei Zhang; Liqun Qu; Xiaoyun Yun; et al. (Inflammation Research, 2023)
Background Rheumatoid arthritis (RA) is an autoimmune inflammation disease characterized by imbalance of immune homeostasis. p53 mutants are commonly described as the guardian of cancer cells by conferring them drug-resistance and immune evasion. Importantly, p53 mutations have also been identified in RA patients, and this prompts the investigation of its role in RA pathogenesis. Methods The cytotoxicity of disease-modifying anti-rheumatic drugs (DMARDs) against p53 wild-type (WT)/mutant -transfected RA fibroblast-like synoviocytes (RAFLSs) was evaluated by MTT assay. Adeno-associated virus (AAV) was employed to establish p53 WT/R211* adjuvant-induced arthritis (AIA) rat model. The arthritic condition of rats was assessed by various parameters such as micro-CT analysis. Knee joint samples were isolated for total RNA sequencing analysis. The expressions of cytokines and immune-related genes were examined by qPCR, ELISA assay and immunofluorescence. The mechanistic pathway was determined by immunoprecipitation and Western blotting in vitro and in vivo. Results Among p53 mutants, p53 R213* exhibited remarkable DMARD-resistance in RAFLSs. However, AAV-induced p53 R211* overexpression ameliorated inflammatory arthritis in AIA rats without Methotrexate (MTX)-resistance, and our results discovered the immunomodulatory effect of p53 R211* via suppression of T-cell activation and T helper 17 cell (Th17) infiltration in rat joint, and finally downregulated expressions of pro-inflammatory cytokines. Total RNA sequencing analysis identified the correlation of p53 R211* with immune-related pathways. Further mechanistic studies revealed that p53 R213*/R211* instead of wild-type p53 interacted with TANK-binding kinase 1 (TBK1) and suppressed the innate immune TBK1–Interferon regulatory factor 3 (IRF3)–Stimulator of interferon genes (STING) cascade. Conclusions This study unravels the role of p53 R213* mutant in RA pathogenesis, and identifies TBK1 as a potential anti-inflammatory target.

Efficient transformation of plastic wastes to H2 and electromagnetic nanocarbon absorbents over molecular-level engineered 3D NiCo/MnO - Dan Xu; Chen Shen; Xingmin Liu; Wenjie Xie; Hui Ding; Marc Widenmeyer; Maximilian Mellin; Fangmu Qu; Aasir Rashid; Guoxing Chen; Emanuel Ionescu; Ye Shui Zhang; et al. (Chemical Engineering Journal, 2023)

Development of the consider cubature Kalman filter for state estimation of hydrological models with parameter uncertainty - Y. Sun; W. Bao; S. Qu; Q. Li; P. Jiang; Z. Zhou; P. Shi (Journal of Hydrology, 2023)

A spatiotemporal deconstruction-based approach for identifying flash drought expansion: Normalized Area-Time Accumulation curve - Ruiqi Chen; Yi Liu; Ye Zhu; Liliang Ren; Yanping Qu; Jason A. Otkin; Vijay P. Singh (Journal of Hydrology, 2023)

Controlled release of pharmaceutical agents using eutectic modified gelatin - Wanwan Qu; Idrees B. Qader; Andrew P. Abbott (Drug Delivery and Translational Research, 2022)
Deep eutectic solvent (DES) is a class of ionic liquids, consisting of a mixture generally formed by combining hydrogen bond donors (HBDs) such as alcohols, amides and carboxylic acids with various quaternary ammonium salts. The decrease in melting points of the constituents is due to the charge delocalization during formation of hydrogen bonding between the hydrogen bond acceptor with the hydrogen bond donor. This can be considered one of the main reasons for increasing solubility and absorption of DESs. Most active pharmaceutical ingredients (APIs) have polar functional groups containing amide, carboxylic acid, alcohol or quaternary ammonium groups. These tend to increase the melting point of the compounds, but they can be used to form eutectic mixtures. While this concept has previously used, the combination of quaternary ammonium salts with amides, carboxylic acids and alcohols can result in large depressions of freezing points and so-called deep eutectic solvents are formed. DESs mix readily with water and so could increase the uptake of APIs. In this study, pharmaceutical deep eutectic solvents (PDESs) are formulated from 3 APIs: imipramine HCl, ascorbic acid and catechol. These PDESs were used to plasticise gelatine. It is shown that the materials formed can be used to increase the rate of API uptake via both oral and transdermal delivery modes. Thus, the concentration of the PDESs in solution reaches the maximum before the pure drugs. Particularly for catechol, after 1 s, the dissolution of the PDESs was more than twice that of the pure drug. Moreover, the transdermal delivery mode uptake of the PDES based on imipramine HCl from the patch after 15 min was found to be 65% compared with just imipramine HCl which released only 20%. Graphical abstract

Anti-Inflammatory and Anti-Oxidant Activity of Ultra-Short Wave Diathermy on LPS-Induced Rat Lung Injury - Q. Wu; M. Qu; P. Zhong; Y. Zeng; J. Wang; Q. Zhang; Ting Wang; D. Liu; L. Yang; J. Zhou; Tong Wang (Bulletin of Experimental Biology and Medicine, 2022)

Critical Risk Indicators (CRIs) for the electric power grid: a survey and discussion of interconnected effects - Judy P. Che-Castaldo; Rémi Cousin; Stefani Daryanto; Grace Deng; Mei-Ling E. Feng; Rajesh K. Gupta; Dezhi Hong; Ryan M. McGranaghan; Olukunle O. Owolabi; Tianyi Qu; Wei Ren; Toryn L. J. Schafer; et al. (Environment Systems and Decisions, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Aquatic food webs in deep temperate lakes: Key species establish through their autecological versatility - Zhishuai Qu; Dominik Forster; Estelle P. Bruni; Daniela Frantal; Barbara Kammerlander; Laura Nachbaur; Gianna Pitsch; Thomas Posch; Thomas Pröschold; Katrin Teubner; Bettina Sonntag; Thorsten Stoeck (Molecular Ecology, 2021)
Microbial planktonic communities are the basis of food webs in aquatic ecosystems since they contribute substantially to primary production and nutrient recycling. Network analyses of DNA metabarcoding data sets emerged as a powerful tool to untangle the complex ecological relationships among the key players in food webs. In this study, we evaluated co‐occurrence networks constructed from time‐series metabarcoding data sets (12 months, biweekly sampling) of protistan plankton communities in surface layers (epilimnion) and bottom waters (hypolimnion) of two temperate deep lakes, Lake Mondsee (Austria) and Lake Zurich (Switzerland). Lake Zurich plankton communities were less tightly connected, more fragmented and had a higher susceptibility to a species extinction scenario compared to Lake Mondsee communities. We interpret these results as a lower robustness of Lake Zurich protistan plankton to environmental stressors, especially stressors resulting from climate change. In all networks, the phylum Ciliophora contributed the highest number of nodes, among them several in key positions of the networks. Associations in ciliate‐specific subnetworks resembled autecological species‐specific traits that indicate adaptions to specific environmental conditions. We demonstrate the strength of co‐occurrence network analyses to deepen our understanding of plankton community dynamics in lakes and indicate biotic relationships, which resulted in new hypotheses that may guide future research in climate‐stressed ecosystems.

Study on crack propagation and shear behavior of weak muddy intercalations submitted to wetting-drying cycles - L. P. He; J. Y. Yu; Q. J. Hu; Q. J. Cai; M. F. Qu; T. J. He (Bulletin of Engineering Geology and the Environment, 2020)

Great journey of Great Tits (Parus major group): Origin, diversification and historical demographics of a broadly distributed bird lineage - Gang Song; Ruiying Zhang; Fernando Machado‐Stredel; Per Alström; Ulf S. Johansson; Martin Irestedt; Herman L. Mays; Bailey D. McKay; Isao Nishiumi; Yalin Cheng; Yanhua Qu; Per G. P. Ericson; et al. (Journal of Biogeography, 2020)
Aim The Pleistocene glacial cycles play a prominent role in shaping phylogeographical patterns of organisms, while few studies have focused on the regional difference of glacial effects. By acquiring comprehensive knowledge of the origin, diversification and historical demography of an intensively studied passerine species complex, Great Tit, we aim to test the regional variation of the Late Pleistocene glaciation impacts on this widely distributed bird lineage. Location Eurasia and associated peninsulas and archipelagos. Taxa Parus major species complex. Methods Phylogeny, divergence times and demographic dynamics were estimated with Bayesian methods. Population structure, genetic diversity and correlation between genetic and physical distances were estimated based on mtDNA variation. Glacial‐to‐present distributional changes were assessed via ecological niche modelling (ENM). Results Five major clades (Central Asia, Eastern Asia, Eastern Himalaya, Northern and Western Eurasia and Southern Asia) were detected, with divergence times ranging 1.57–0.50 million years ago. Genetic diversity values and Bayesian skyline plots suggest that the three eastern clades had a deeper population history. A more complex geographic structure was observed in East Asia. Demographic expansion during the last glacial cycle was indicated for all five clades. ENM results showed broad conservatism of traits related to climate tolerances, and generally broader and more continuous distributional patterns under glacial conditions. Main Conclusions The Great Tit complex probably originated in Southeast Asia. Geographic barriers, such as the deserts of Central Asia and the Qinghai–Tibet Plateau appear to be related to the lineage divergence. Late Pleistocene climate cycles influenced both demographic dynamics and divergence, especially in terms of east–west differences in relation to geographic complexity.

Effect of EM microbial agent on aerobic composting for dairy cattle manure - G. Qu; Y. Cai; P. Lv; X. Ma; R. Xie; Y. Xu; P. Ning (International Journal of Environmental Science and Technology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Spatiotemporal extremes of temperature and precipitation during 1960–2015 in the Yangtze River Basin (China) and impacts on vegetation dynamics - Lifang Cui; Lunche Wang; Sai Qu; Ramesh P. Singh; Zhongping Lai; Rui Yao (Theoretical and Applied Climatology, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Effect of centrifugal force on the development of articular neocartilage with bovine primary chondrocytes - J. Prittinen; J. Ylärinne; J. Piltti; S. S. Karhula; L. Rieppo; S. P. Ojanen; R. K. Korhonen; S. Saarakkala; M. J. Lammi; C. Qu (Cell and Tissue Research, 2019)

Mucosa-associated microbiota signature in colorectal cancer - R. Gao; C. Kong; L. Huang; H. Li; X. Qu; Z. Liu; P. Lan; J. Wang; H. Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Nucleoside analogue 2’-C-methylcytidine inhibits hepatitis E virus replication but antagonizes ribavirin - Changbo Qu; Lei Xu; Yuebang Yin; Maikel P. Peppelenbosch; Qiuwei Pan; Wenshi Wang (Archives of Virology, 2017)

A zoogeographical boundary between the Palaearctic and Sino‐Japanese realms documented by consistent north/south phylogeographical divergences in three woodland birds in eastern China - Gang Song; Ruiying Zhang; Yanhua Qu; Zhiheng Wang; Lu Dong; Anton Kristin; Per Alström; Per G. P. Ericson; David M. Lambert; Jon Fjeldså; Fumin Lei (Journal of Biogeography, 2016)
Aim The location of zoogeographical boundaries in eastern China has long been the subject of debate. To identify any north/south genetic divergence between the Palaearctic and Sino‐Japanese realms proposed by previous studies, we conducted a comparative phylogeographical study involving three passerine species with wide latitudinal distributions in eastern China. Location Eastern China. Methods Two mitochondrial genes and three nuclear introns were amplified and sequenced. Population structures were analysed using intra‐specific phylogeny, tcs networks, AMOVA and structure inferences. We tested for evidence of genetic barriers based on pairwise differences. Lineage divergences, demographic dynamics and gene flow between lineages were estimated using Bayesian methods. Results A congruent north/south phylogeographical divergence was identified for three species. A geographical barrier was inferred at c . 40° N in eastern China. The population sizes of the northern and southern lineages have both been stable through the late Pleistocene, while multiple divergences were inferred during the early and middle Pleistocene. Main conclusions Our results suggest a general phylogeographical break in north‐eastern China, coinciding with the Palaearctic/Sino‐Japanese boundary. Physical blocking of the Yan Mountains and fragmentation of suitable habitat during glacial stages between the north and south probably acted together to provide long‐lasting barrier effects. Our comparative phylogeographical approach demonstrates that the Palaearctic/Sino‐Japanese boundary may represent a gene‐flow barrier even within widespread species.

Short-term variability in the dates of the Indian monsoon onset and retreat on the southern and northern slopes of the central Himalayas as determined by precipitation stable isotopes - Wusheng Yu; Tandong Yao; Lide Tian; Yaoming Ma; Rong Wen; Lochan P. Devkota; Weicai Wang; Dongmei Qu; Tek B. Chhetri (Climate Dynamics, 2016)

Global Drivers of Russian Timber Harvest - Sai Liang; Sen Guo; Joshua P. Newell; Shen Qu; Yu Feng; Anthony S.F. Chiu; Ming Xu (Journal of Industrial Ecology, 2016)
Summary Russian forest resources are important for global carbon cycling. In contrast to traditional analyses that focus on the harvest and direct use of Russian timber resources (a.k.a. production‐based accounting), this study investigates how the consumption of nations drives Russian timber harvest (a.k.a. consumption‐based accounting or the Russian timber footprint). China is the biggest direct importer and final consumer of Russian timber. The United States, Japan, and major European countries directly import relatively small amounts of Russian timber, but serve to drive large amounts of Russian timber harvest through their final consumption. Through structural path analysis, individual supply chain paths are delineated to show linkages between Russian timber harvest and the final consumption of nations. Findings of this study inform consumption‐side measures for Russian forest conservation, for example, taking shared responsibility and improving the production efficiency of key sectors in consuming nations.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Multi-pathway assessment of human health risk posed by polycyclic aromatic hydrocarbons - Changsheng Qu; Bing Li; Haisuo Wu; Shui Wang; John P. Giesy (Environmental Geochemistry and Health, 2015)

The influence of geological events on the endemism of East Asian birds studied through comparative phylogeography - Yanhua Qu; Gang Song; Bin Gao; Qing Quan; Per G. P. Ericson; Fumin Lei (Journal of Biogeography, 2015)
Aim East Asia is known for its exceptionally high biological diversity and endemism. Various geological and climatic events during the Pliocene and Pleistocene have been invoked to explain this high endemism, and these processes have had different impacts on different organisms. Herein, we investigate the relative role of these historical processes in the genetic evidence for endemism of intraspecific lineages of two East Asian species: the grey‐cheeked fulvetta ( Alcippe morrisonia ) and the red‐headed tree babbler ( Stachyridopsis ruficeps ). Location East Asia. Methods We studied the genetic structure based on mitochondrial and nuclear DNA and evaluated the phylogeographical lineages using coalescent species tree approaches. The influences of different historical processes on diversification among phylogeographical lineages were analysed using coalescent models. We tested correlations between ecological divergence and phylogeographical splits. Results The genetic structure analysis and species tree estimation revealed three deeply divergent lineages within both species. One lineage is endemic to the mountains of Southwest China and the other to Taiwan. Coalescent simulations suggested that lineage diversification mostly occurred during the late Pliocene. Within this time frame, uplift of the mountains of Southwest China and formation of the island of Taiwan are geological events consistent with the geographical isolation and ecological niche divergence of these phylogeographical lineages. Main conclusions Our results suggest that the main driver of avian endemism in East Asia was the formation of new montane and island habitats following the uplift of the mountains of Southwest China and formation of the island of Taiwan in the Pliocene. However, the populations in the two regions were affected differently by the climatic oscillations during the Pleistocene. The mountains of Southwest China were climatically stable during glaciations, allowing populations to persist throughout the Pleistocene and maintain their genetic uniqueness. In contrast, glaciations resulted in lowered sea levels, allowing dispersal between the island of Taiwan and mainland China, thus obscuring the genetic endemism of the Taiwanese populations.

Response to letter to the editor by Cohen et al. (2014) “Re: Waalkes et al.: Lung tumors in mice induced by “whole-life” inorganic arsenic exposure at human-relevant doses, Arch Toxicol, 2014” - Michael P. Waalkes; Wei Qu; Erik J. Tokar; Grace E. Kissling; Darlene Dixon (Archives of Toxicology, 2014)

Elevated plasma sphingomyelin (d18:1/22:0) is closely related to hepatic steatosis in patients with chronic hepatitis C virus infection - J.-F. Li; F. Qu; S.-J. Zheng; H.-L. Wu; M. Liu; S. Liu; Y. Ren; F. Ren; Y. Chen; Z.-P. Duan; J.-L. Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Lung tumors in mice induced by “whole-life” inorganic arsenic exposure at human-relevant doses - Michael P. Waalkes; Wei Qu; Erik J. Tokar; Grace E. Kissling; Darlene Dixon (Archives of Toxicology, 2014)

Elkton: A New Potato Variety with Resistance to Internal Heat Necrosis and Hollow Heart and Suitable for Chipping Directly from the Field in the Southern United States - K. G. Haynes; D. M. Gergela; X. S. Qu; M. W. Peck; G. C. Yencho; M. E. Clough; M. R. Henninger; D. E. Halseth; G. A. Porter; P. C. Ocaya; L. Zotarelli; S. R. Menasha; et al. (American Journal of Potato Research, 2014)

Long‐term isolation and stability explain high genetic diversity in the Eastern Himalaya - Yanhua Qu; Per G. P. Ericson; Qing Quan; Gang Song; Ruiying Zhang; Bin Gao; Fumin Lei (Molecular Ecology, 2014)
China's Southwest Mountainous Region in Eastern Himalaya is a ‘biodiversity hotspot’ of global interest for conservation. Yet little is known about what has driven this unique diversity. The dramatic topography of the Southwest Mountainous Region resulting from the tectonic uplift during the late Pliocene leads to dramatic ecological stratification, which creates physical barriers to migration and isolates organisms into different subregions and mountain systems. This agrees with the observation that the phylogeographical patterns found in four species of birds ( A lcippe morrisonia , S tachyridopsis ruficeps , P arus monticolus and A egithalos concinnus ) distributed in this region are characterized by deep splits between lineages that coalesce between 0.8 and 2.1 Ma. Unlike other regions at this latitude, the Southwest Mountainous Region was largely unaffected by the Pleistocene glaciations. Genetically isolated populations of these birds could thus be maintained throughout the Pleistocene in these rather stable montane environments. In comparison, we found radically different phylogeographical patterns in populations of the same four species distributed in the adjacent lowland, the Central China region. This region has a distinctly different geological history with dramatic, climate‐induced shifts in vegetation during the Pleistocene. Here, we found a considerably less geographical structure in the genetic variation and a much younger coalescence time (0.3–0.7 Ma). We also found evidence of genetic bottlenecks during the glacial periods and gene flow during the interglacial expansions. We conclude that the high genetic diversity in the Southwest Mountainous Region results from a long‐term in situ diversification within these evolutionary isolated and environment stable montane habitats.

Quantitative and qualitative characteristics of dissolved organic matter from eight dominant aquatic macrophytes in Lake Dianchi, China - Xiaoxia Qu; Li Xie; Ying Lin; Yingchen Bai; Yuanrong Zhu; Fazhi Xie; John P. Giesy; Fengchang Wu (Environmental Science and Pollution Research, 2013)

Metallothionein blocks oxidative DNA damage in vitro - Wei Qu; Jingbo Pi; Michael P. Waalkes (Archives of Toxicology, 2013)

Role of reactive oxygen species in the antibacterial mechanism of silver nanoparticles on Escherichia coli O157:H7 - Hengyi Xu; Feng Qu; Hong Xu; Weihua Lai; Y. Andrew Wang; Zoraida P. Aguilar; Hua Wei (BioMetals, 2012)

Influence of Temperature on Solvent-Mediated Anhydrate-to-Hydrate Transformation Kinetics - Haiyan Qu; Tommy Munk; Claus Cornett; Jian X. Wu; Johan P. Bøtker; Lars P. Christensen; Jukka Rantanen; Fang Tian (Pharmaceutical Research, 2011)

Structural consequences of a 3′ → 3′ DNA interstrand cross-link by a trinuclear platinum complex: unique formation of two such cross-links in a 10-mer duplex - Yun Qu; My-Chau Tran; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2009)

In Silico Construction of a Protein Interaction Landscape for Nucleotide Excision Repair - Nancy Tran; Ping-Ping Qu; Dennis A. Simpson; Laura Lindsey-Boltz; Xiaojun Guan; Charles P. Schmitt; Joseph G. Ibrahim; William K. Kaufmann (Cell Biochemistry and Biophysics, 2009)

Expression of the bacteriophage T4 lysozyme gene in tall fescue confers resistance to gray leaf spot and brown patch diseases - Shujie Dong; H. David Shew; Lane P. Tredway; Jianli Lu; Elumalai Sivamani; Eric S. Miller; Rongda Qu (Transgenic Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic variation in C57BL/6 ES cell lines and genetic instability in the Bruce4 C57BL/6 ES cell line - Elizabeth D. Hughes; Yun Yan Qu; Suzanne J. Genik; Robert H. Lyons; Christopher D. Pacheco; Andrew P. Lieberman; Linda C. Samuelson; Igor O. Nasonkin; Sally A. Camper; Margaret L. Van Keuren; Thomas L. Saunders (Mammalian Genome, 2007)

Molecular mapping of stripe rust resistance gene YrCH42 in Chinese wheat cultivar Chuanmai 42 and its allelism with Yr24 and Yr26 - G. Q. Li; Z. F. Li; W. Y. Yang; Y. Zhang; Z. H. He; S. C. Xu; R. P. Singh; Y. Y. Qu; X. C. Xia (Theoretical and Applied Genetics, 2006)

Fluorescence Imaging for Real-Time Monitoring of High-Intensity Focused Ultrasound Cardiac Ablation - Cheri X. Deng; Fujian Qu; Vladimir P. Nikolski; Yun Zhou; Igor R. Efimov (Annals of Biomedical Engineering, 2005)

Postglacial colonization of the Tibetan plateau inferred from the matrilineal genetic structure of the endemic red‐necked snow finch, Pyrgilauda ruficollis - YAN HUA QU; PER G. P. ERICSON; FU MIN LEI; SHOU HSIEN LI (Molecular Ecology, 2005)
Most phylogeographical studies of postglacial colonization focus on high latitude locations in the Northern Hemisphere. Here, we studied the phylogeographical structure of the red‐necked snow finch Pyrgilauda ruficollis , an endemic species of the Tibetan plateau. We analysed 879 base pairs (bp) of the mitochondrial cytochrome b gene and 529 bp of the control region in 41 birds from four regional groups separated by mountain ranges. We detected 34 haplotypes, 31 of which occurred in a single individual and only three of which were shared among sampling sites within regional groups or among regional groups. Haplotype diversity was high ( h = 0.94); nucleotide diversity was low (ð = 0.00415) and genetic differentiation was virtually non‐existent. Analyses of mismatch distributions and geographically nested clades yielded results consistent with contiguous range expansion, and the expansion times were estimated as 0.07–0.19 million years ago (Ma). Our results suggest that P. ruficollis colonized the Tibetan plateau after the extensive glacial period (0.5–0.175 Ma), expanding from the eastern margin towards the inner plateau. Thus, in contrast to many of the postglacial phylogeographical structures known at high latitudes, this colonization occurred without matrilineal population structuring. This might be due to the short glacial cycles typical of the Tibetan plateau, adaptation of P. ruficollis to cold conditions, or refugia and colonized habitat being semicontinuous and thus promoting population mixing.

Abundance of IFN-? and IFN-? mRNA in blood of resistant and susceptible chickens infected with Marek?s disease virus (MDV) or vaccinated with turkey herpesvirus; and MDV inhibition of subsequent induction of IFN gene transcription - P. Qur; C. Rivas; K. Ester; R. Novak; W. L. Ragland (Archives of Virology, 2005)

Evaluation of water and energy budgets in regional climate models applied over Europe - S. Hagemann; B. Machenhauer; R. Jones; O. B. Christensen; M. Dqu; D. Jacob; P. L. Vidale (Climate Dynamics, 2004)

Bromodeoxyuridine DNA fiber technology in plants: replication origins and DNA synthesis in tobacco BY-2 cells under prolonged treatment with aphidicolin - A.-H. Qulo; J.-P. Verbelen (Protoplasma, 2004)

Cooperative effects in long-range 1,4 DNA-DNA interstrand cross-links formed by polynuclear platinum complexes: an unexpected syn orientation of adenine bases outside the binding sites - Yun Qu; Neel J. Scarsdale; My-Chau Tran; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2003)

Molecular mapping of the reverse thermo-sensitive genic male-sterile gene (rtms1) in rice - J. H. Jia; D. S. Zhang; C. Y. Li; X. P. Qu; S. W. Wang; V. Chamarerk; H. T. Nguyen; B. Wang (Theoretical and Applied Genetics, 2001)

Key results and implications from phase 1(c) of the Project for Intercomparison of Land-surface Parametrization Schemes - A. J. Pitman; A. Henderson-Sellers; C. E. Desborough; Z.-L. Yang; F. Abramopoulos; A. Boone; R. E. Dickinson; N. Gedney; R. Koster; E. Kowalczyk; D. Lettenmaier; X. Liang; et al. (Climate Dynamics, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

True potato seed in China: Past, present and future - Song Bofu; Qu Dong Yu; P. Vander Zaag (American Journal of Potato Research, 1987)